Pelatihan Penelitian Tindakan Kelas untuk Meningkatkan Kompetensi Guru - Nizaruddin Nizaruddin; Muhtarom Muhtarom; Aryan Eka Prastya Nugraha; Fenny Roshayanti; Sumarno Sumarno (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of implementing this service activity is to provide training and assistance to teachers at SMP N 1 Pecangaan and SMP N 2 Pecangaan in classroom action research (CAR). The output to be achieved in this program is that teachers at SMP N 1 Pecangaan and SMP N 2 Pecangaan attend CAR training so that they are able to make proposals, carry out CAR in class, are able to compile CAR reports and can write scientific articles for publication. The training is carried out in groups with an andragogy approach. The training method is carried out using the following methods: lectures and questions and answers, demonstrations, exercises and practices. Simultaneously the training was followed by mentoring activities in the preparation of proposals, implementation of open classes and assistance in the preparation of reports and articles. Training and mentoring activities through IbM Class Action Research activities for teachers of SMP N 1 Pecangaan and SMP N 2 have implications for teachers' understanding of the implementation of CAR to their ability to compile published articles.